Contemporary trends and new competitiveness strategies in hotel industry - Maksimović, Goran; Sekulić, Dejan; Petrović, Aleksandar; Dragičević, Darko (Hotel and Tourism Management, 2017)
The hotel industry in modern business conditions, characterized by the networking of all key factors, is changing rapidly. Today, with „one-click? all information about hotels, tourist offer and price of services is available to tourists. The growth of megabrends through acquisitions, the growth of private rentals and the digitalization of consumer services are the trends that have been changing and shaping the hotel industry for the past few years. These trends affect hotel operators to develop new strategies for attracting consumers and retaining them. The aim of this paper is to explore what the key trends that have shaped and changed the hotel industry in recent years are, the changes that have occurred, what can be expected in the coming years and the ways hoteliers can adapt.